"At Home in Trans-America: American Studies at the Linguistic and Conceptual Borders" - Šesnić, Jelena (2007)
The most recent trend in American studies is termed the "transnational turn". The author argues that originally this development was promoted by ethnic studies as a new trend in the discipline and has continued in a number of related disciplines, such as border studies, postcolonial theory, critical race studies, area studies. At the same time, some integrity, consistency and a sense of limitations has to be maintained if the discipline of American studies is to retain its viability.
ENG